Trajetórias de escolarização de estudantes com Transtorno do Espectro Autista - Machado de Paula, Cristiane Aparecida (2024)
The presence of people with disabilities in Higher Education Institutions, which has been gradually established in the Brazilian context, encourages knowledge of the factors that permeated and favored the schooling process in Basic Education. In this sense, the present study had the general objective of investigating the schooling trajectories of two students with Autism Spectrum Disorder (ASD) enrolled in an undergraduate course, based on their statements about their school experience. The specific objectives of the research were: Identify the barriers encountered in the school trajectory of young people with ASD from entering Early Childhood Education to completing Basic Education; know the support systems to which students had access throughout their schooling process and which favored the appropriation of school knowledge; examine how concrete living conditions can impact the educational trajectory. The theoretical-methodological framework that underpins the research is the Historical-Cultural Theory of Human Development, with an emphasis on the concept of experience/perejivanie, taken as a unit of analysis in explaining the relationships between subject and social environment in the process of cultural development. Two young students participated in the research, one female and one male, aged between 21 and 22 years old, enrolled and attending an undergraduate course at a Federal Institute. The methodological procedure used to collect data consisted of conducting interviews. Some written records of care given to family members and to the subjects themselves, prepared upon entry into the Higher Education Institution, were used as supporting material. The data was organized into three axes, namely: Support systems and educational supports; barriers and accessibility; diagnoses and their effects on the schooling process. In general, the data show how concrete living conditions affect the school trajectory and point to how the participation of research subjects in school spaces throughout Basic Education, with the appropriation of historically accumulated knowledge, favored entry into Higher Education. They reveal the intense struggle of family members in defense of better access to schooling for their children with Autism Spectrum Disorder. It was possible to verify that the factors that favored the academic trajectory of students with ASD in Basic Education refer to: family support; to teaching relationships based on work with knowledge experienced in the school context; to intersectoral relations involving, above all, the education and health sectors. We consider the school experience attributed meaning as a factor that permeated the trajectory of these students from Basic Education to Higher Education. It was also possible to understand how the social situation of development and disability marks the experience and influences the formation of personality.